Extraction and immunomodulatory activity of the polysaccharide obtained from Craterellus cornucopioides - Zhang, Caixuan; Shu, Ying; Li, Yang; Guo, Mingzhu (Frontiers in Nutrition, 2022)
In this study, we investigated the structural features of the polysaccharide obtained from Craterellus cornucopioides (CCP2) by high-performance liquid chromatography, Fourier transform infrared spectroscopy, ion chromatography and scanning electron microscopy (SEM). The results showed that CCP2 was a catenarian pyranose that principally comprise mannose, galactose, glucose, and xylose in the ratio of 1.86: 1.57: 1.00: 1.14, with a molecular weight of 8.28×104 Da. Moreover, the immunoregulation effect of CCP2 was evaluated both in vitro and in vivo. It displayed a remarkable immunological activity and activation in RAW264.7 cells by enhancing the phagocytosis of macrophages in a dose-dependent manner without showing cytotoxicity at the concentrations of 10-200 μg/mL in vitro. Additionally, Histopathological analysis indicated the protective function of CCP2 against immunosuppression induced by cyclophosphamide (Cy). Meanwhile, the intake of CCP2 had better immunoregulatory activity for immunosuppression BALB/c mice model. After prevention by CCP2, the spleen and thymus weight indexes of BALB/c mice model were significantly increased (200.0 mg kg−1 d-1 and 400.0 mg kg−1 d-1). The RT-qPCR and Western Blot results provided comprehensive evidence that the CCP2 could activate macrophages by enhancing the production of cytokines (IL-2, IL-6 and IL-8) and upregulating the protein expression of cell membrane receptor TLR4 and its downstream protein kinase (TRAF6, TRIF and NF-κB p65) production of immunosuppressive mice through TLR4-NFκB p65 pathway. The results demonstrated that CCP2 could be a potential prebiotic and might provide meaningful information for further research on the immune mechanism.